People Perception on Business Opportunities of Banana Restaurants of Tikapur: Evidence from Structural Equation Modelling - Singh, Bharat Jung; Devkota, Niranjan; Dhakal, Krishna; Mahato, Surendra; Paudel, Udaya Raj (Journal of Business and Social Sciences Research, 2022)
Banana restaurant is a new concept in Nepal where the products are made using banana only which gives the first mover advantage in product development and has less explored in Nepal. Therefore, this study aims to analyse consumers’ perception and business opportunity of banana restaurant in Tikapur, Kailali, Nepal. This study adopted explanatory research, and 203 samples were collected from consumers of banana restaurants. In addition, data were collected using structured questionnaire by using KOBO Toolbox. Thus, the obtained data were analysed by using both descriptive and inferential methods. Findings indicate that consumers perceive products of banana restaurant positively and are enjoying the variety of products. Likewise, SEM results indicate that psychological, economic and social characteristics are significant to innovativeness and risk taking, whereas innovativeness and risk taking are significant to managerial performance. Banana restaurant has been contributing with local employment and shows the high level of business opportunity of the banana products in the market of Tikapur (Kailali, Western Nepal).